Splash plasma channels produced by picosecond laser pulses in argon gas for laser wakefield acceleration - Y. Mizuta; T. Hosokai; S. Masuda; A. Zhidkov; K. Makito; N. Nakanii; S. Kajino; A. Nishida; M. Kando; M. Mori; H. Kotaki; Y. Hayashi; et al. (Physical Review Special Topics. Accelerators and Beams, 2012)
Short-lived, ∼10  ps, deep plasma channels, with their lengths of ∼1  mm and diameters of ∼20  μm, are observed and characterized in Ar gas jets irradiated by moderate intensity, ∼10^{15–16}  W/cm^{2}, laser pulses with a duration from subpicosecond to several picoseconds. The channels, upon 2D particle-in-cell simulations including ionization, fit well in the guiding of high intensity femtosecond laser pulses and, therefore, in laser wakefield acceleration with a controllable electron self-injection.